A coastal settlement from the Late Stone Age in Lofoten - Kovačević, Nikola; Kvalheim, Alice Sunde; Niemi, Anja Roth (Tromura, 2026)
In 2022, the Arctic University Museum of Norway investigated two sites from the Late Stone Age in Tjeldbergvika in Vågan municipality. Site 1 is considered to represent multiple occupations over a long period of time, with two phases of use in the middle part of the Late Stone Age (3700-3600 BCE, and around 3000 BCE), one in the centuries around 2000 BCE, and one in the pre-Roman Iron Age. Traces of two possible house foundations and relatively extensive cultural layer deposits have been identified. Site 2 is dated to the period between approximately 4200 and 3300 BCE. Four house foundations were identified here, which appear to have been relatively solidly built. At the same time, the artefact material from is very limited, and there is no indication that the houses were used simultaneously. This may indicate that the area was visited and used by small groups and over shorter periods, possibly by a single household/boat crew at a time. The artefacts include fishing sinkers, floats, and sharpened slate points and knives, which testify to fishing and the capture of marine mammals. A rock shelter was examined in connection with site 2. It probably served as a temporary residence or shelter, with documented use in the Roman Iron Age, Merovingian times, and during the 17th–18th centuries.
Keywords: Archaeological excavation; archaeology; Neolithic; Late Stone Age; Lofoten; settlement; slate tools; ceramics